Two cases of disseminated infection following live organism anti-cancer vaccine administration in cancer patients. (July 2018) - Denham, James D.; Lee, Dae Hyun; Castro, Manuel; Pandya, Shuchi; Aslam, Sadaf; Nanjappa, Sowmya; Greene, John N.
Highlights: We present two cases of vaccine-induced disease in cancer patients. History of recent vaccination can lead to expedited treatment. It is unclear if treatment of infection reduces efficacy of the vaccine. Abstract: Vaccines containing live attenuated bacterial or viral organisms are currently being investigated as potential therapy for locally advanced or metastatic cancers. However, the use of such live organisms in an immunocompromised population, such as patients who recently or are currently receiving chemotherapy, raises the concern that these organisms can themselves disseminate and cause frank infection. We report a hereunto unreported phenomenon of anti-cancer vaccines (containing live attenuated organisms) leading to frank, disseminated infection. We submit that occurrence of this phenomenon must be watched for by all members of the interdisciplinary cancer treatment team.